2024
DOI: 10.1002/advs.202308538
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Injectable Polyurethane Underwater Adhesive with Fast Bonding and Hemostatic Properties

Xiaolei Guo,
Xin Zhao,
Lei Yuan
et al.

Abstract: Underwater adhesives with injectable, organic solvent‐free, strong, fast adhesion, and hemostatic properties have become an urgent need in biomedical field. Herein, a novel polyurethane underwater adhesive (PUWA) inspired by mussels is developed utilizing the rapid post‐cure reaction of isocyanate esterification without organic solvents. The PUWA is created through the injectable two component curing process of component A (biocompatible polyurethane prepolymer) and component B (dopamine modified lysine deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Furthermore, both MXene/Que-WPU and Que-WPU exhibited excellent blood compatibility. The cytocompatibility of the film patches is essential for wound healing . It was evaluated via an in vitro MTT antitumor bioassay using HaCaT cells (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both MXene/Que-WPU and Que-WPU exhibited excellent blood compatibility. The cytocompatibility of the film patches is essential for wound healing . It was evaluated via an in vitro MTT antitumor bioassay using HaCaT cells (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…The cytocompatibility of the film patches is essential for wound healing. 39 It was evaluated via an in vitro MTT antitumor bioassay using HaCaT cells (Figure S5). The results revealed that HaCaT cell viability (%) was above 93.39% in a concentration range of 0.50 mg/mL.…”
Section: In Vitro Hemolysis Assay Andmentioning
confidence: 99%
“…28–32 Among the various hydrogels, polyurethane-based hydrogels have exhibited exceptional performance. 32–36 Recently, hydrogels exhibited great potential for postoperative anti-adhesions. Particularly, physical isolation that involves the obstruction of contact between the surgical site and its surrounding tissue is convenient for injectable hydrogels.…”
Section: Introductionmentioning
confidence: 99%